Continuous Synthesis of Ag/TiO2 Nanoparticles with Enhanced Photocatalytic Activity by Pulsed Laser Ablation. (16th November 2017) - Zhou, Rui; Lin, Shengdong; Zong, Huixin; Huang, Tingting; Li, Fengping; Pan, Jiahong; Cui, Jingqin
Abstract : A facile and environmental friendly synthesis strategy based on pulsed laser ablation has been developed for potential mass production of Ag-loaded TiO2 (Ag/TiO2 ) nanoparticles. By sequentially irradiating titanium and silver target substrates, respectively, with the same 1064 nm 100 ns fiber laser, Ag/TiO2 particles can be fabricated. A postannealing process leads to the crystallization of TiO2 to anatase phase with high photocatalytic activity. The phase composition, microstructure, and surface state of the elaborated Ag/TiO2 are characterized by X-ray diffraction (XRD), energy dispersive X-ray (EDX), field emission scanning electron microscope (FESEM), transmission electron microscope (TEM), and X-ray photoelectron spectroscopy (XPS) techniques. The results suggest that the presence of silver clusters deposited on the surface of TiO2 nanoparticles. The nanostructure is formed through laser interaction with materials. Photocatalytic activity evaluation shows that silver clusters could significantly enhance the photocatalytic activity of TiO2 in degradation of methylene blue (MB) under UV light irradiation, which is attributed to the efficient electron traps by Ag clusters. Our developed Ag/TiO2 nanoparticles synthesized via a straightforward, continuous, and green pathway could have great potential applications in photocatalysis.